The Role of Blood Flow in Corpus Luteum Measured by Transvaginal Two-Dimensional and Three-Dimensional Ultrasound in the Prediction of Early Intrauterine Pregnancy Outcomes - Han, Huijuan; Mo, Xinhai; Ma, Yuqin; Zhou, Yuqing; Zhang, Bo (Frontiers in Pharmacology, 2019)
Objective: The purpose of this study was to to explore the application of transvaginal two-dimensional and three-dimensional power Doppler ultrasound in pregnancy corpus luteum to predict the final result of early intrauterine pregnancy. Methods: This is a prospective observational cohort study. 600 early intrauterine pregnant women in Shanghai Changning Maternity and Infant Health Hospital were selected as the research objects from January 2015 to December 2015. According to the follow-up of 12 weeks, these pregnant women were divided into the normal pregnancy group (Group A, n=512) and the terminational pregnancy group (Group B, n=88). They all underwent both transvaginal two-dimensional ultrasound and three-dimensional power Doppler ultrasound to obtain relevant parameters of corpus luteum, namely the average diameter of the corpus luteum (D), resistance index (RI), pulsatility index (PI), corpus luteum volume (V), vascularization index (VI), blood flow index (FI), vascularized blood flow index (VFI). Among them, V, VI，FI and VFI were calculated with the virtual organ computer-aided analysis method. Receiver operator characteristic (ROC) curves were drawn. The corresponding diagnostic cut-off, sensitivity and specificity were calculated and compared. Results: Compared with Group A, the D, V, VI, FI and VFI of corpus luteum in group B were statistically significant lower while RI and PI were statistically significant higher (P <0.05). The diagnostic cut-off values in the prediction of early intrauterine pregnancy outcomes were D: 14.48, RI: 0.56, PI: 0.81, V: 3.89, VI: 21.48, FI: 38.99 and VFI: 10.21 respectively, and the sensitivity and specificity were D (99.2%、67.0%), RI (98.9%,65.0%), PI (78.4%、89.1%), V (95.1%、78.4%), VI (74.%、90.9%), FI (91.8%、90.9%) and VFI (93.9%、87.5% ) respectively. The area under the ROC curve of the combined index (RI + FI) was 0.963, which was no significantly higher compared with the single index, and both the sensitivity and specificity were 94.3%. Conclusion: Both transvaginal two-dimensional and three-dimensional ultrasonography are of high diagnostic value in predicting the early intraunterine pregnancy outcomes. Keywords: Transvaginal two-dimensional ultrasound, Transvaginal three-dimensional ultrasound, Receiver operator characteristic curve, Early intrauterine pregnancy, Corpus luteum